Activin‐A in Diabetes‐Induced Cardiac Malformations in Embryos. (28th May 2013) - Zhao*, Zhiyong
<x xml:space="preserve">Abstract</x> BACKGROUND Heart defects are the most common abnormalities in infants of diabetic mothers. Cardiac malformation is associated with altered expression of the genes in the transforming growth factor β system, including inhibin βA, which forms activin‐A as a homodimer and functions through its effectors, Smad2 and Smad3. This study aimed to investigate the role of activin‐A in diabetes‐induced cardiac malformations. METHODS Diabetes mellitus in female mice (C57BL/6J) was induced via intravenous injection of streptozotocin. The expression of inhibin βA protein and phosphorylation of Smad2 and Smad3 in the embryonic hearts were examined using immunohistochemical, in situ proximity ligation, and immunoblot assays. Embryos and endocardial cushions of nondiabetic mice were cultured in a high concentration of glucose and treated with activin‐A. Mitosis was examined using BrdU incorporation assay and immunohistochemistry of phosphorylated histone H3. Migration of the endocardial cells was assessed using a collagen‐based cell migration assay. RESULTS The levels of inhibin βA expression and Smad2 and Smad3 activation were significantly reduced by maternal diabetes. Treatment with activin‐A significantly increased cell proliferation in the myocardium and migration of endocardial cells, compared with those in vehicle‐treated high glucose group, to the level in the euglycemic control group. CONCLUSIONS Maternal diabetes suppresses the expression of inhibin βA protein, as well as the activation of Smad2 and Smad3. Activin‐A rescues cell proliferation in the myocardium and migration of the endocardial cells suppressed by hyperglycemia. The activin‐Smad2/3 signaling system appears to play a role in cardiac malformation in diabetic embryopathy. Birth Defects Res (Part B) 98:260–267, 2013. © 2013 Wiley Periodicals, Inc.